TINJAUAN YURIDIS KEDUDUKAN HUKUM PENANGGUNG YANG BERITIKAD BAIK DIKAITKAN DENGAN KREDIT MACET (STUDI PADA BANK PANIN TBK YOGYAKARTA) - , MUHAMMAD DANI RAMDHAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is aim to discover the legal position of insurer (borgtocht) in personal insurance binding related with bad debt. Especially to discover existence of legal position of insurer and creditor, also legal protection for the insurer that had good intention in personal guarantee binding while the bad debt is occurred. This research is an empirical normative legal research which uses empirical juridical and qualitative descriptive analysis. Research result found that First, legal position of insurer is subsidiary due to agreement in personal guarantee binding is not stand alone which means that the agreement is accessoir. Subsidiary determination in implementation of the debt fulfillment that is the insurer could just implementing his obligation as insurer when main debtor already fulfill or perform his obligation of debt payment to creditor first. The insurer in the insurance has special rights, the rights given by Legislation as form of legal protection for the insurer, the rights are right to claim acquittal first of debtor wealth, right to share or divide the debt, right to ward and right to request dismissed from insurance / responsibility due to blocked in performing subrogation as effect of creditor fault. That Second, in credit lending or credit extension practice in bank transaction, bank as creditor requires security, therefore, and bank will request insurance from the main debtor, both in form of material insurance and additional insurance. This is merely to ensure security in term of credit repayment by the debtor in future days. Usually in this matter bank will provide promises that advantaging their position and provide security to common debtor which contain of claiming special right of the insurer. Every contract or agreement must be based on a good intention, insurer with good intention will protected by Legislation.